Identity and image in the city marketing - Piskóti, István; Nagy, Szabolcs (Marketing & Menedzsment, 2019)
Our paper shows a comprehensive view of theoretical and practical aspect of city marketing and its planning model. Based on the competence-based paradigm, the focus is placed on steps in marketing planning, the 2P-mix instead of 4Ps. The central elements of the model are decisions and actions concerning city identity and city image. Methodology of city-audit-structure, which was tested in practice, is an important tool for decision makers in public marketing.